2012
DOI: 10.1016/j.otsr.2011.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Infected total hip arthroplasty revision: One- or two-stage procedure?

Abstract: Level III; prospective case control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 18 publications
3
62
0
10
Order By: Relevance
“…The final results of the two stage procedure are satisfactory in terms of function, pain and eradication of infection (9.2%). Two-stage reimplantations have previously been found to successfully eradicate infection in 84-100% [1][2][3], which is consistent with our observations. A systematic review and metaanalysis based on aggregate published data found the reinfection rate after one-or two-stage revision to be approximately 8% [2].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The final results of the two stage procedure are satisfactory in terms of function, pain and eradication of infection (9.2%). Two-stage reimplantations have previously been found to successfully eradicate infection in 84-100% [1][2][3], which is consistent with our observations. A systematic review and metaanalysis based on aggregate published data found the reinfection rate after one-or two-stage revision to be approximately 8% [2].…”
Section: Discussionsupporting
confidence: 92%
“…The treatment goal is to attempt limb salvage, eradicate infection and preserve joint function. The prognosis for resolving infectious processes in hip arthroplasties ranges from 84 to 100% with current surgical techniques [1][2][3]. The two most common surgical procedures are one-and two-stage revisions.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports (Table 3), some surgeons routinely perform one-stage revision THAs, with infection control rates in six studies reported to be 77-100 % [1,2,12,22,23,25]. Others, including our study, selected one-stage revision THA depending on patient requirements and showed infection control rates of 76-100 % in the eight studies [13,[15][16][17][18][19]26]. These rates were similar to those reported in studies only performing onestage revision THAs.…”
Section: Discussionsupporting
confidence: 86%
“…First, the study sample size was small, involving only 55 individuals. Obtaining a large series from a single institution is difficult, and there have been only five literature reports involving relatively large patient series (>50 patients) from a single institution [15][16][17][18][19]. We considered an analysis from a single The values show the mean (range)…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and management of these infections are complex (3)(4)(5)(6), with outcome contingent on detection and identification of the causative microorganism(s) (6,7). The gold standard, culture of synovial fluid, periprosthetic tissue, and/or the implant itself, has been associated with a range of sensitivities (8)(9)(10)(11)(12)(13)(14) and has various turnaround times of up to 2 weeks.…”
mentioning
confidence: 99%